Design principles for platinum nanoparticles catalysing electrochemical hydrogen evolution and oxidation reactions: edges are much more active than facets. Issue 44 (1st November 2017) - Zalitis, C. M.; Kucernak, A. R.; Sharman, J.; Wright, E.
Abstract : Improving the performance of hydrogen evolution and oxidation reactions using precious metal catalysts is key in reducing the cost of electrolysers and fuel cells. Abstract : Improving the performance of hydrogen evolution and oxidation reactions using precious metal catalysts is key in reducing the cost of electrolysers and fuel cells. By considering the performance of these reactions as a function of platinum particle size (2.1–15 nm) under high mass transport conditions in acids, we find that the activity is composed of two components which vary in a defined way with the particle size. Geometrical considerations and electrokinetic modelling suggest that these two components correspond to the response of edges/vertices and the response of facets (Pt(100) and Pt(111)). Edges and vertices are much more active towards the hydrogen reaction. This assignment also rationalises the poor performance of platinum in alkaline environments. We predict that "ideal" particles made up of only edges/vertices would allow fuel cells and electrolysers to operate with only 1 μgPt cm −2 – about two to three orders of magnitude lower than what is currently used.